Explaining international co-authorship in global environmental change research - Arlette Jappe-Heinze (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2006)
This paper maps the domain of earth and environmental sciences (EES) and investigates the relationship between cognitive problem structures and internationalisation patterns, drawing on the concepts of systemic versus cumulative global environmental change (GEC) and mutual task dependence in scientific fields. We find that scientific output concentration and internationalisation are significantly higher in the systemic GEC fields of Meteorology & Atmospheric Sciences and Oceanography than in the cumulative GEC fields Ecology and Water Resources. The relationship is explained by stronger mutual task dependence in systemic GEC fields. In contrast, the portion of authorships with developing, emerging and transition countries among all international publications is larger for Water Resources than for three other fields, consistent with the most pressing needs for STI capacity development in these countries.
urn:nbn:de:0011-n-454560
Keywords: 330